Effects of bronchodilation on biomarkers of peripheral airway inflammation in COPD. (July 2018) - Santus, Pierachille; Radovanovic, Dejan; Mascetti, Susanna; Pauletti, Alessia; Valenti, Vincenzo; Mantero, Marco; Papi, Alberto; Contoli, Marco
Graphical abstract: Abstract: Peripheral airway inflammation and dysfunction are key elements in the pathogenesis of COPD. The exhaled alveolar fraction of nitric oxide (CANO) is an indirect biomarker of lung peripheral inflammation. We tested whether inhaled long-acting bronchodilators (LABA) can affect CANO and we evaluated correlations with lung mechanics in patients with COPD. Two-centre, randomised, double blind, crossover study including COPD patients with moderate-to-severe airflow obstruction. Following a pharmacological washout, multi-flow exhaled fraction of NO (FENO), plethysmography, lung diffusion (DLCO), single breath nitrogen washout test and dyspnoea were measured in a crossover manner at baseline and 30, 60 and 180 min following administration of salmeterol (Sal) or formoterol fumarate (FF). (ClinicalTrials.gov, number NCT01853787). Fort-five patients were enrolled (median age: 71.8 years; 84.4% males). At baseline, CANO correlated with airway resistances (r = 0.422), residual volume/total lung capacity (RV/TLC; r = 0.375), transfer factor (r= -0.463) and forced expiratory volume in 1 s (FEV1; r= -0.375, all P < 0.01). After LABA administration, we found a significant reduction of FENO that reached statistical significance at 180'; no difference was found between FF and S. Consistently, a significant reduction of CANO was documented at 60' and 180' compared to baseline for both FF and S (P < 0.01 and P < 0.05, respectively). Changes in CANO were correlated with changes in vital capacity (r=-44; P < 0.001) and RV/TLC (r = 0.56; P < 0.001), but not FEV1. In COPD, direct correlations were found between the levels of CANO and the magnitude of peripheral airway dysfunction. LABA reduced CANO levels. The reduction was associated with improvement in functional parameters reflecting air trapping.